2020
DOI: 10.3390/ijms21020658
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Transcripts in Apolygus lucorum (Meyer-Dür) Exposed to Different Temperature Coefficient Insecticides

Abstract: The existence of a temperature effect of insecticides frustrated the control of the green plant bug Apolygus lucorum (Meyer-Dür). Previous studies mostly focused on the application of insecticides, but the underlying mechanism remains incompletely understood. Here, we report a transcriptome profiling of A. lucorum treated by three kinds of temperature coefficient insecticides (TCIs) (positive TCI: imidacloprid, negative TCI: b-cypermethrin and non-effect TCI: phoxim) at 15 °C, 25 °C and 35 °C by using next- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Previously, Guo et al (2018) showed that elevated temperatures, especially a moderately-high temperature (31 • C), were responsible for enhancing the tolerance of thiamethoxam in Bemisia tabaci by inducing or the specific activities of detoxication enzyme genes, which is consistent with our results. Similar results with high temperatures and insecticide tolerance were reported in Apolygus lucorum (Meyer-Dur) (An et al, 2020), Agasicles hygrophila (Zhang et al, 2018), and Musca domestica (Scott & Georghiou, 1984).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previously, Guo et al (2018) showed that elevated temperatures, especially a moderately-high temperature (31 • C), were responsible for enhancing the tolerance of thiamethoxam in Bemisia tabaci by inducing or the specific activities of detoxication enzyme genes, which is consistent with our results. Similar results with high temperatures and insecticide tolerance were reported in Apolygus lucorum (Meyer-Dur) (An et al, 2020), Agasicles hygrophila (Zhang et al, 2018), and Musca domestica (Scott & Georghiou, 1984).…”
Section: Discussionsupporting
confidence: 86%
“…High temperatures and insecticides can occur simultaneously during L. trifolii outbreaks, but previous studies have largely ignored the synergistic effects that can accompany these two forms of stress. Climate change, especially global warming, can always increase the frequency of extreme weather events and impact the development, reproduction and survival of insects (Bale et al, 2002;Savage et al, 2004;Frazier, Huey & Berrigan, 2006) and may also induce a heat shock response in insects (Huang, Wang & Kang, 2009;Feng et al, 2010;Sun et al, 2014;An et al, 2020). High temperatures have been becoming a vital menace to the volatility, stability, degradation and metabolism of insecticides when extreme high temperature climate appears frequently, which makes global warming a pivotal factor influencing insect survival and adaption (Goel et al, 1987;Johnson, 1990;Scott, 1995;Bale et al, 2002;Gordon, 2005;An et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that the environmental temperature may have strong effects on the xenobiotic response of the green plant bug Apolygus lucorum to various pesticides. This result implies that the insecticide temperature coefficient plays an important role in detoxification efficiency (An et al, 2020).…”
Section: Transcriptome Studies Of Insect Xenobiotic Responsementioning
confidence: 91%
“…Besides these classical detoxification enzymes, the enrichment analyses using databases such as GO, KEGG, and COG indicated the involvement of target gene-encoded proteins and enzymes that belong to other biological processes or functions in the xenobiotic response in different insects. These processes include amino acid metabolism, posttranslational modification, ribosomal biogenesis, cytoskeleton formation, lipids, carbohydrate metabolism, and so on (An et al, 2020;Derecka et al, 2013;X. Liu et al, 2016;N.…”
Section: Transcriptome Studies Of Insect Xenobiotic Responsementioning
confidence: 99%